Effects of multiferroics BFO and HMO nanoparticles addition on structural, electrical and superconducting properties of YBa₂Cu₃O₇₋ᵹ - Bahboh, Abdalla Imhmed (2019)
The YBa₂Cu₃O₇₋ᵹ (Y-123) superconductor is one of the materials that have been considered to have the potential of making a significant impact on technology, in particular on the issue of critical current density. The main problem that restricts the technology applications of bulk Y-123 is the low grain boundary conductivity due to weak links and poor flux pinning, causing low Jc in the presence of magnetic field. In this work two types of multiferroics, namely BiFeO3 and HoMnO3 having nano-sized particles were incorporated into Y-123 to form composites with the compositions; ( YBa₂Cu₃O₇₋ᵹ)1-x(BFO or HMO)x with x = 0.0025, 0.005, 0.0075, 0.01, 0.03 0.05, 0.07, and 0.10. The composites were fabricated by introducing sol-gel synthesized BFO and coprecipitation synthesized HMO during solid state reaction process of Y- 123. Samples were characterized using XRD, FESEM, EDX, four-point probe, AC susceptometer, ESR and Impedance analyzer. From the XRD results, single phase Y-123 having orthorhombic structure were observed. On the other hand, the BFO showed single phase of BiFeO3 belonging to hexagonal structure ,while the HMO showed two mixed phases of HoMnO3 in about 85% of the total phase with hexagonal structure and HoMn2O5 in about 15% with orthorhombic structure. XRD patterns manifested that all composite samples, could be indexed to orthorhombic crystal structure, while Y-211 was detected as minor phase. Besides, YBa2BiO6 and YFe2O4 were detected in samples with BFO addition and phases YBaMn2O5, YBaMn2O6 and HoBa2Cu4O8 were detected in HMO added samples. FESEM images showed that grain size of Y-123, BFO and HMO are 11.0, 0.065 and 0.085 μm respectively. The grain size decreased as additions increased. EDX analysis showed accurate match for standard peak position for Y, Ba, Cu and O for Y-123. Spectra also showed the presence of agglomerated particulates related to Fe and Bi compounds embedded between Y-123 grains in BFO added samples. Similarly agglomerated particulates related to Mn and Ho phases were detected residing between Y-123 grains. The Y-123 sample exhibited good metallic behavior in the normal state. TC(R=0) for Y-123 was 92 K and TC(onset) was 97 K. The superconducting behavior of Y-123/BFO samples showed a decrease in Tc(R=0) as the addition increased. The composite with x = 0.01 showed highest TC(R=0) of 90 K and degraded to 44 K at x = 0.10. When added with HMO the highest TC(R=0) was 91 K at x = 0.0025, then gradually decreased to 83 K for x=0.1. The AC susceptibility measurement for the pure Y-123 showed sharp curve of diamagnetism transition in the real part (χʹ) which is exhibited by two-step transitions related to the intragrain and intergrain couplings. The imaginary part (χʹʹ) demonstrates two peaks attributed to intrinsic behavior of intragrain and intergrain couplings. The intergranular critical current density, JC(TP) , and Josephson current, I0, of pure Y-123 are 16.54 Acm-2 and 40.59 μA respectively. AC susceptibility curves in the real part (χʹ) for the added BFO samples manifested inclined transitions for all samples, whereas the samples with less BFO contents of x = 0.0025 and 0.005 showed the strongest intergrain couplings. While the AC susceptibility curves for the samples with HMO showed sharp transition for the samples with x = 0.0025, 0.005 and 0.0075. In both systems, I0, and JC(TP) of the composite samples were higher than that of pure Y- 123. Maximum I0 and JC(TP) were observed when x = 0.0025 in both addition systems. The maximum JC(TP) observed for BFO and HMO samples are 18.07 Acm-2 and 21.96 Acm-2 respectively. Dielectric parameters εr′ and εr′ʹ decreased as the frequency increased for all samples in pure and composites. The εr versus frequency measurements showed an increase in εr′ and εr′ʹ values for all added samples as compared to Y-123. The highest values for εr′ and εr′ʹ were obtained when x = 0.1 with the highest loss at lower frequency. The highest values of εr′ and εr′ʹ for (Y-123), (Y-123/BFO) and (Y-123/HMO) are (2.05×102, 1.56×103), (3.67×103, 22.56×103) and (5.15×103, 24.66×103) respectively. Nyquist plot of complex impedance (Zʹ-Zʹʹ) were analysed where two semi arc circulars representing grain and grain boundary effects were deduced in both systems. From ESR measurements all pure Y-123, BFO and HMO added samples showed spectra consisting of two peaks. The g-factor for the composite samples changed in different manner from the Y-123 sample, while it decreased at lower concentrations (x ≤ 0.0075) and increased at higher concentrations (x ≥ 0.01) in BFO added samples, it increased at lower concentrations (x ≤ 0.01) and increased at higher concentrations (x ≥ 0.03) in HMO added samples.